2020
DOI: 10.2196/19857
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of App-Based Contact Tracing for COVID-19: Cross-Country Survey Study

Abstract: Background The COVID-19 pandemic is the greatest public health crisis of the last 100 years. Countries have responded with various levels of lockdown to save lives and stop health systems from being overwhelmed. At the same time, lockdowns entail large socioeconomic costs. One exit strategy under consideration is a mobile phone app that traces the close contacts of those infected with COVID-19. Recent research has demonstrated the theoretical effectiveness of this solution in different disease sett… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
445
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(491 citation statements)
references
References 19 publications
35
445
10
1
Order By: Relevance
“…Overall, our findings also correspond well with other international population surveys of DPT app use, most of which were performed before [ 23 - 29 ], and some after app release [ 30 ]. For example, several studies confirmed the finding that higher education status [ 25 ], and younger age [ 23 ] were associated with a higher willingness to use DPT apps. Of note, these characteristics could reflect the profile of typical early adopters of technology [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our findings also correspond well with other international population surveys of DPT app use, most of which were performed before [ 23 - 29 ], and some after app release [ 30 ]. For example, several studies confirmed the finding that higher education status [ 25 ], and younger age [ 23 ] were associated with a higher willingness to use DPT apps. Of note, these characteristics could reflect the profile of typical early adopters of technology [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our observations of technical problems and persistent privacy concerns as reasons for nonuse or uninstallations of the SwissCovid app are consistent with those of a study in Australia [ 30 ], which reported similar user complaints. Furthermore, (a lack of) government trust emerged as a strong influencing factor for app usage in our and other surveys [ 23 ]. For example, approximately 11% of the respondents of the Australian survey cited government mistrust as a reason for not using the app [ 30 ].…”
Section: Discussionmentioning
confidence: 81%
“…These technical solutions are designed to enable faster identification and isolation of infected persons, but users' concerns about privacy and governmental handling of personal data may hinder their application. It has been reported that the acceptance of app-based contact tracing is increased in persons who have comorbidities and always carry their phone [14]. Usually, young people like professional football players have greater technically affinity and should not encounter any difficulties in the installation of smartphone applications.…”
Section: Discussionmentioning
confidence: 99%
“…Residents’ perception of privacy and trust in public authorities can vary from culture to culture, which can impact the captured definition of individual privacy preservation [ 39 - 41 ]. A survey conducted in five other countries (ie, France, Germany, Italy, the United Kingdom, and the United States) found that people in settings with stronger public privacy and security concerns are relatively less supportive of app-based contact tracing, and individuals with less trust in public authorities are also less supportive [ 46 , 47 ].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%
“…Second, the delays in data sharing could allow the spread of COVID-19 to continue, increasing the time and effort needed to contain it [ 9 , 46 , 47 ]. If infectious individuals and their close contacts could be identified with efficacy, the effectiveness of digital health could be increased remarkably, and limited health care resources could thus be prioritized for the quarantining and treatment of the most severe cases [ 42 ].…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%